Late Ancient Christian Anxiety over Islamic Geographies of Containment: Two Examples - Chance E. Bonar (Religions, 2024)
In the seventh and eighth centuries CE, Christians across the Mediterranean were experiencing the consequences of the rise of Islam and its expansion. With this challenge to Christian hegemony in the eastern Mediterranean, Christian writers began to ask about the effect of Islamic expansion on their own lives, practices, and worlds to come. In this article, I aim to contextualize two examples of how late ancient Christians questioned their ability to remain Christian in the face of both Islamic captivity and assimilation: 3 Apocryphal Apocalypse of John (3 Apocr. Apoc. John) and Anastasius of Sinai’s (d. ca. 700) Questions and Answers (Questions). I divide this article into three sections. First, I place Christian anxiety over Islamic rule in conversation with Stephanie Camp’s concept of the “geography of containment” to explore how some late ancient Christians understood themselves to be geographically and spatially limited by imprisonment or enslavement. I also provide an overview of recent scholarship on Christian responses to early Islamic expansion and anxiety over enslavement, imprisonment, captivity, and assimilation to Islam. Finally, I turn to 3 Apocr. Apoc. John and Anastasius’s Questions to analyze how late ancient Christians turned to monks and patriarchs to find answers regarding the uncertainty of Christian identity under Islamic rule.